PERAN PENGAWAS MADRASAH DALAM PENILAIAN KINERJA KEPALA MADRASAH DI KABUPATEN BLITAR - Hasan, Abdur Rosyid; Bachtiar Firdaus, Ahmad; Nur Efendi (re-JIEM (Research Journal of Islamic Education Management), 2023)
Performance assessment of madrasah principals is important to be carried out as a form of evaluation so that it can foster the seriousness of madrasah principals to improve the quality of performance, quality of service, and other progressive efforts. The research has a descriptive qualitative approach with a field study. The research data were collected using interview techniques, as well as documentation, and then analyzed using an interactive model. The results showed that madrasah supervisors in the Blitar district conducted annual and four-year performance assessments of madrasah principals. The assessment starts from the preparation stage by providing instruments and media for uploading documents to madrasah principals, the implementation stage with document verification and madrasah visits, at the reporting stage, the assessment results are given to the head of the madrasah education section at the District Ministry of Religious Affairs Office and the Head of Madrasah Education Division at the Provincial Ministry of Religious Affairs Office. Cooperation by all parties in the madrasah will greatly help the assessment process run smoothly, but in its implementation, there are also inhibiting factors such as lack of resources, lack of understanding of the assessment criteria, and the number of madrasahs supervised by one madrasah supervisor.